Livestock epigenetics - Khatib, Hasan (Hoboken : Wiley-Blackwell, 2012)
Livestock Epigenetics is the first book to review advances in the understanding of the molecular basis of epigenetic mechanisms in gene expression in livestock species. Epigenetics impact many economically important traits from growth and development to more efficient reproduction and breeding strategies. The book opens with a broad introductory chapter that discusses the importance of an understanding of epigenetics to efficient and sustainable livestock production. In subsequent chapters the role of epigenetics in specific aspects of animal production are reviewed. The final chapter will pro.
Epigenetics of mammalian gamete and embryo development / Nelida Rodriguez-Osorio, Sule Dogan, and Erdogan Memili -- Epigenetics of cloned pre-implantation embryos of domestic animals / Xiuchun Cindy Tian and Sadie L. Marjani -- Roles of imprinted genes in fertility and promises of the genome-wide technologies / Ashley Driver, Wen Huang, and Hasan Khatib -- Sheep as an experimental model for human art: novel insights on phenotypic alterations in art-derived sheep conceptuses / Pasqualino Loi [and others] -- The DLK1-DIO3 imprinted gene cluster and the callipyge phenotype in sheep / Christopher A. Bidwell [and others] -- Genomic imprinting and imprinted gene clusters in the bovine genome / Ikhide G. Imumorin, Sunday O. Peters, Marcos De Donato -- Imprinting in genome analysis: modelling parent-of-origin effects in QTL studies / Suzanne Rowe, Stephen Bishop and DJ de Koning -- Epigenetics and animal health / Juan Luo, Ying Yu, and Jiuzhou Song -- Epigenetics and microRNAs in animal health / Fei Tian and Jiuzhou Song -- Nutrients and epigenetics in bovine cells / Congjun Li.
Includes bibliographical references and index.
Keywords: Livestock -- Genetics; Livestock -- Embryology; Epigenesis; Epigenesis; Livestock -- Embryology; Livestock -- Genetics; Agriculture; MEDICAL -- Veterinary Medicine -- Food Animal; MEDICAL -- Veterinary Medicine -- Small Animal; Epigenesis, Genetic; Livestock -- genetics; Livestock -- embryology; Electronic books; Electronic books